"Geosynthetic reinforcement stiffness for analytical and numerical modeling of reinforced soil structures" by Richard J. Bathurst and Fahimeh M. Naftchali, geotextiles and geomembranes, 49 (2021) 921–940. Issue 4 (August 2022) - Mirmoradi, S.H.; Ehrlich, M.
Highlights: The maximum reinforcement loads, Tmax, calculated using the finite difference method in the paper under discussion are significantly different with those presented by Huang et al. (2010). The summations of Tmax calculated in these analyses are different by a factor of ∼3. The corresponding active state condition is theoretically considered as a lower bound in the calculation of Tmax for the reinforcement layers, in which the load is not influenced by the combination of the facing stiffness and toe restriction.